Extensive Molecular Dynamics Simulations Show That Canonical G8 and Protonated A38H(+) Forms Are Most Consistent with Crystal Structures of Hairpin Ribozyme - Mlýnský, Vojtěch (2010)
The hairpin ribozyme is a prominent member of the group of small catalytic RNAs (RNA enzymes or ribozymes) because it does not require metal ions to achieve catalysis. Biochemical and structural data have implicated guanine 8 (G8) and adenine 38 (A38) as catalytic participants in cleavage and ligation catalyzed by the hairpin ribozyme, yet their exact role in catalysis remains disputed. To gain insight into dynamics in the active site of a minimal self-cleaving hairpin ribozyme, we have performed extensive classical, explicit-solvent molecular dynamics (MD) simulations on timescales of 50-150 ns. Starting from the available X-ray crystal structures, we investigated the structural impact of the protonation states of G8 and A38, and the inactivating A−1(2′-methoxy) substitution employed in crystallography. Our simulations reveal that a canonical G8 agrees well with the crystal structures while a deprotonated G8 profoundly distorts the active site. Thus MD simulations do not support a straightforward participation of the deprotonated G8 in catalysis. By comparison, the G8 enol tautomer is structurally well tolerated, causing only local rearrangements in the active site. Furthermore, a protonated A38H(+) is more consistent with the crystallography data than a canonical A38. The simulations thus support the notion that A38H(+) is the dominant form in the crystals, grown at pH 6. In most simulations, the canonical A38 departs from the scissile phosphate and substantially perturbs the structures of active site and S-turn. Yet, we occasionally also observe formation of a stable A−1(2′-OH)…A38(N1) hydrogen bond, which documents the ability of the ribozyme to form this hydrogen bond, consistent with a potential role of A38 as general base catalyst. The presence of this hydrogen bond is, however, incompatible with the expected in-line attack angle necessary for self-cleavage, requiring a rapid transition of the deprotonated 2′-oxyanion to a position more favorable for in-line attack after proton transfer from A−1(2′-OH) to A38(N1). The simulations revealed a potential force field artifact, occasional but irreversible formation of ‘ladder-like’, underwound A-RNA structure in one of the external helices. Although it does not affect the catalytic center of the hairpin ribozyme, further studies are under way to better assess possible influence of such force field behavior on long RNA simulations.